Rekayasa Pendinginan Alami Rumah Samin Kontemporer - Garda Ady Yasa; Agung Murti Nugroho (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
The architecture of the house is formed due to the needs,comfort and local culture. The number of traditional houses replaced by modern house without thinking about the comfort, needs and culture of residents who will also have an impact on the absence of sustainable architecture. As the object of this research study is Klopodhuwur Village which is a traditional settlement of Samin people. Therefore, this research has engineered a contemporary natural cool house which can be an alternative to a simple, environmentally friendly village house for the future. The method used in this research is evaluative descriptive, simulation, and pragmatic engineering. Evaluative methods are used to look at thermal problems so that they can be used as a reference for engineering. Experimental simulation methods are used to validate measurement results and engineers samin contemporary passive cooling houses. Finally, the pragmatic method is used as a solution to the overall problem of architectural needs and convenience. The results of the passive cooling engineering of samin contemporary houses show that the temperature is in the comfort range of Karyono 2001 (24.2 ° C-29.2 ° C) and neutral temperature (24.2 ° C-29.2 ° C). While in the aspect of comfort and space requirements for the present and future of the house is also engineered in the contemporary Samin house.